In Vitro Comparison of Two Neonatal ECMO Circuits Using a Roller or Centrifugal Pump With Three Different In‐Line Hemoconcentrators for Maintaining Hemodynamic Energy Delivery to the Patient. Issue 4 (11th January 2018) - Force, Madison; Moroi, Morgan; Wang, Shigang; Palanzo, David A.; Kunselman, Allen R.; Ündar, Akif
Abstract: The objective of this study was to compare three different hemoconcentrators (Hemocor HPH 400, Mini, and Junior) with two different neonatal ECMO circuits using a roller or a centrifugal pump at different pseudo‐patient pressures and flow rates in terms of hemodynamic properties. This evidence‐based research is necessary to optimize the ECMO circuitry for neonates. The circuits used a 300‐mL soft‐shell reservoir as a pseudo‐patient approximating the blood volume of a 3 kg neonate, two blood pumps, and a Quadrox‐iD Pediatric oxygenator with three different in‐line hemoconcentrators (Hemocor HPH 400, Mini, and Junior). One circuit used a Maquet H20 roller pump and another circuit used a Maquet RotaFlow centrifugal pump. The circuit was primed with lactated Ringer's solution followed by heparinized packed red blood cells with a hematocrit of 40%. The pseudo‐patient's pressure was manually maintained at 40, 60, or 80 mm Hg and the flow rate was maintained at 200, 400, or 600 mL/min with a circuit temperature of 36°C. Pressure and flow data was recorded using a custom‐made data acquisition device. Mean pressures, diverted blood flow, pressure drops, and total hemodynamic energy (THE) were calculated for each experimental condition. The roller pump and centrifugal pump performed similarly for all hemodynamic properties with all experimental conditions. The Hemocor HPH Junior hemoconcentrator added the highest resistance to the circuit. The Hemocor HPH Junior provided the highest circuit pressures, lowest diverted blood flow, highest pressure drop across the circuit, and highest THE generated by the pump. The Hemocor HPH 400 added the least resistance to the circuit, providing the lowest circuit pressures, more diverted flow, lowest pressure drop, and the lowest THE generated by the pump. However, the THE delivered to the patient was the same for the three hemoconcentrators. While the three hemoconcentrators performed differently in terms of hemodynamic properties throughout the circuit, the THE transmitted to the patient was similar for all three hemoconcentrators due to the consistent pseudo‐patient's pressure that was manually maintained for each trial. While the THE delivered to the patient indicates similar perfusion for these patients with any of the three hemoconcentrators, the differences in added resistance to the circuit may impact the decision of which hemoconcentrator is used. There was no clinically significant difference between the two circuits with the roller versus centrifugal pump in terms of hemodynamic properties in this study. Further in vivo research is warranted to confirm our findings.